Un pic asa de ajutor
![Un Pic Asa De Ajutor class=](https://ro-static.z-dn.net/files/dbb/e6fb1e0506ea9bd52da3bdefc76e9dd4.jpg)
Răspuns:
f:R→R ; f(x) = [tex]\frac{12-4x}{3}[/tex]
a) f(1) = [tex]\frac{12-4}{3} = \frac{8}{3}[/tex]
f(2) = [tex]\frac{12-8}{3}= \frac{4}{3}[/tex]
f(3) = [tex]\frac{12-12}{3}=0[/tex]
f(4) = [tex]\frac{12-16}{3}=-\frac{4}{3}[/tex]
⇒ f(1)·f(2)·f(3)·f(4) = 0
b) Gf ∩ Ox = {A}
Gf ∩ Ox ⇒ f(x) = 0 ⇒ [tex]\frac{12-4x}{3}[/tex] = 0 ⇒ x = 3 ⇒ A(3,0)
Gf ∩ Oy = {B}
Gf ∩ Oy ⇒ f(0) = y = [tex]\frac{12}{3}[/tex] = 4 ⇒ B(0,4)
AB = [tex]\sqrt{(Xa-Xb)^{2}+(Ya-Yb)^{2} } = \sqrt{(3-0)^{2}+(0-4)^{2} } = \sqrt{25 } = 5[/tex]